THE APPLICATION OF PARTICIPATED DOCTRINE IN CORRUPTION (STUDY OF DECISION ON CORRUPTION CRIMINAL ACT COURT AT IA JAYAPURA DISTRICT COURT) - Rohrohmana, Basir (INDONESIAN JOURNAL OF CRIMINAL LAW STUDIES, 2017)
Decision of Criminal Act of Corruption Court at the IA Jayapura District Court Number 05/Pid.Sus-TPK/2015/PN.Jap, and (2) Decision Number 06/ Pid.Sus-TPK/2015/PN.Jap. Both decisions show the application of participated doctrine, both in the indictment, the prosecution of the prosecutor, and the basis of the judges judgment to result the decisions to the offenders.Â There are 2 (two) findings to be disclosed in the analysis of these decisions are (1) the participated doctrine which is applied apparently in their application are within separate prosecution areas between the two indictments, thereby treating the participants in the participated doctrine equally with the independent offender, even impressed as a convergence offense, (2) with prosecution in the indictment, the prosecutor and judge in applying the participated doctrine in these two decisions tend to be restrictive in view that the offender is compared to the dader not as part of the producers entity (verzamen term) in which there are qualities of offenders who can be distinguished between pleger, doenpleger, medepleger, uitlokker or medeplichtigheid.